Hubungan Kecanduan Game dengan Gangguan Tidur Pada Remaja di MTsS Al-Washliyah 27 Sei Rampah - Pratiwi, Anatasya Diani; Nafessa, Nafessa (Jouska: Jurnal Ilmiah Psikologi, 2025)
This study aims to find out the correlation between game addiction and sleep disturbance in MTsS Al – Washliyah 27 Sei Rempah. The method used in this research is quantitative method. The research subjects used were 186 students. Thesampling technique used in this research is Purposive Sampling technique with certain criteria. The hypothesis put forward in this study is there is a positive correlation between game addiction and adolescent sleep disturbance with the assumption that the higher the game addiction, the higher the sleep disturbance in adolescents. This study uses the Likert scale to measure game addiction and sleep disturbance variables. In this study using Pearson Product Moment Correlation DataAnalysis techniques using the SPSS version 22.00 application. Based on the results of data analysis obtained P sig (0.000) 0.05 with rxy = 0.945 which indicates that the hypothesis is accepted. Thus, it can be stated that there is a significant positive relationship between game addiction and sleep disturbance. The correlation between game addiction and sleep disturbance is high. Gameaddictionhasaneffect of 89,4% on sleep disorder.